Optical Characterization of a 20 Layer AlGaAs/GaAs Multiple Quantum Wells - Ali, Luqman; Cho, Janghyun; Byeon, Clare Chisu; Song, Jin Dong; Jo, Hyun-Jun; Kim, Jong Su (KOREAN PHYSICAL SOC, 2018)
A 20-layer Al0.4Ga0.6As/GaAs multiple quantum well (MQW) sample was deposited on a GaAs substrate by using the molecular beam epitaxy (MBE) method. Optical characterization was carried out by power and temperature dependent photoluminescence (PL) for excitation powers ranging from 40 mW to 120 mW and for temperatures ranging from 11 K to 300 K. At low temperature (LT), only one dominant peak appeared in the spectrum with a much higher PL intensity and less broadening with a significant red shift ( 2.4 nm) of the peak as the excitation power was increased. As the temperature was raised to room temperature (RT), increasing excitation power linearly increased the PL with relatively no significant red shift of the main peak, which may be attributed to heavy-hole transitions near the band edge. As the temperature increased, an additional shoulder peak at higher energy are more apparent because the relative intensity of the main peak decreased. Broadening of the shoulder peak was more significant, and its full width at half maximum (FWHM) increased 4.6 nm (> 25% increase). The shoulder peak at higher energy, which is hidden under the high intensity main peak at LT, presumably indicates relative increase in light-hole transitions due to thermal transport as the temperature increases.
Keywords: MOLECULAR-BEAM EPITAXY; TEMPERATURE-DEPENDENCE; GAAS SUPERLATTICES; PHOTOLUMINESCENCE; HETEROSTRUCTURES; ENERGY